Performance of PMMA/Ta2O5 Composites as Medical Radiation Shielding: WinXCom and MCNP6 Studies - Mustafa Çağlar (Journal of Advanced Research in Natural and Applied Sciences)
The growing reliance on radiation in contemporary applications underscores the imperative to safeguard individuals and the environment from harmful consequences. To mitigate the adverse effects of radiation, polymer composites have begun to garner interest from researchers as potential lead-free shielding materials, largely due to their distinctive attributes, including flexibility, lightness, and environmental benignity. In this study, the gamma radiation shielding capacity of polymethyl methacrylate (PMMA) composites reinforced with varying proportions of Ta₂O₅ (5%, 10%, and 20% wt) was investigated through the utilization of Windows version of photon cross sections on a personal computer (WinXCom) software and the Monte Carlo N-Particle 6 (MCNP6) code. The alignment of the WinXCom and MCNP6 results, despite their different methodologies, provides a robust and reliable understanding of the radiation shielding performance of these composites. The present study investigated the radiation attenuation properties of PMMA/Ta₂O₅ composites about shielding coefficients, including mass attenuation coefficients (MAC), half-value layer (HVL), and effective atomic number (Zeff). The findings indicated that all composites demonstrated enhanced shielding performance compared to pure PMMA. The PMMA/20% Ta₂O₅ composite exhibited MAC values of 1.22-, 1.29-, and 1.28-fold greater than those observed in the silicon-based composites. The MAC increase was observed in the PMMA/20% Ta₂O₅ composite at an energy of 81 keV. The PMMA/20% Ta₂O₅ composite demonstrated the most effective radiation shielding properties. In light of these findings, the PMMA/20% Ta₂O₅ composite can be regarded as a flexible, lightweight, and environmentally friendly shielding material, reassuring these composites' reliability in practical applications.